SUBJECTIVE SLEEP QUALITY IN ELITE WOMENS INTERNATIONAL SOCCER PLAYERS PRIOR TO AN INTERNATIONAL MATCH. Issue 4 (1st February 2017) - Boyce, Stephen; McKenna, Michael; White, Andrew; Davies, Oliver; Dixon, Mark; Elliott, Niall
Abstract : Background: Sleep has been found to have many recuperative and restorative effects on an athlete's recovery and preparation for a match. In international soccer it is common that players have to sleep in unfamiliar locations (e.g. hotel) prior to matches however little is known about the quality of sleep achieved in a hotel compared with at home. Objective: To assess the quality of sleep in elite women's international soccer players prior to a domestic international fixture in comparison to sleep at home. Design: Prospective observational study. Setting: Scotland women's soccer national squad. Participants: Elite women international soccer players. Interventions: 21 female international soccer player's sleep quality was monitored in the weeks before and during four different domestic international camps with the use of a mobile application that was filled out each morning immediately after awakening. Main Outcome Measurements: The sleep quality was assessed using a subjective 10-point scale with 1 being negative and 10 being positive. For differences in sleep quality, an independent t-test was used to compare means. Statistical significance was set at p<0.05. Results: There was no significant difference when comparing sleep quality at home with that of in a hotel in the lead up to a women's home international soccer match (7.44±1.32 vs. 7.36±1.16, p=0.39). Conclusions: The findings of the present study indicate that the subjective sleep quality of female soccer players is not reduced in a hotel prior to a domestic international match and is not compromising recovery and preparation for the match. Further research is required to determine whether this is the same for away international fixtures involving travel.